Advances in service and industrial robotics : proceedings of the 26th International Conference on Robotics in Alpe-Adria-Danube Region, RAAD 2017 /: proceedings of the 26th International Conference on Robotics in Alpe-Adria-Danube Region, RAAD 2017. ([2018]) - Unknown
No abstract available